TARIK-MENARIK KEPENTINGAN DALAM LEGISLASI OMNIBUS LAW UNDANG-UNDANG CIPTA KERJA - Ichwan Ahnaz Alamudi (Fakultas Hukum Universitas Primagraha, 2023)
Studies in this study found that the government as policy makers make efforts to form regulations with the concept of omnibus law that is so many laws will be simplified with one law only. There are several laws that are considered to overlap, namely the licensing cluster, in the academic paper of the job creation law, there are eighteen regulations that are trying to be simplified. The method of research that the author tries to do in this study with a juridical-normative approach to political law. The results of this study indicate that the idea of omnibus law job creation law is a phenomenon of complexity related to investment in Indonesia, the complexity occurs on how to be able to bring investors to invest in Indonesia and finally the government issued a policy of omnibus law UU no. 11 of 2020 concerning Job Creation which aims to bring the investment climate in Indonesia in a healthy direction, so it needs to be supported by good and clear legal certainty. Keywords: Omnibus Law, Policy, Investment.